Erzählte Kulturgeschichten zu Skidoo von Alex Capus - Virant, Špela (Vestnik za tuje jezike, 2019)
The article focusses on the text Skidoo: A Journey Through the Ghost Towns of the American West, by the Swiss author Alex Capus, in order to point out some specific features of his literary work. The first part of the article shows those features of this short literary text that are congruent with the set schemes of the literary biography and travelogue, and underlines those that differ from them. It continues with an analysis of the relation between the text and the pictures integrated in the book. In the final part, Skidoo is compared to selected works that speak about the cultural history of America from a European point of view, starting with Hector St. John de Crevecoeur's Letters from an American Farmer, continuing with texts by Alexis de Tocqueville, Jean Baudrillard and Tzvetan Todorov. This comparison shows the different forms of discourse used in these works, and makes it possible to consider aspects of Skidoo that are easily overlooked, if only traditional genre categories are applied. In particular, Todorov's concept of l'histoire exemplaire, applied to Skidoo, makes it possible to read Capus' stories as part of a narrative cultural history that does not celebrate the conquest of a continent, but elevates the individual with all his faults and failures.
Keywords: biografije; Capus, Alex; kulturna zgodovina; nemška književnost; potopisi; švicarska književnost